2021
DOI: 10.7554/elife.64045
|View full text |Cite
|
Sign up to set email alerts
|

A novel ATP dependent dimethylsulfoniopropionate lyase in bacteria that releases dimethyl sulfide and acryloyl-CoA

Abstract: Dimethylsulfoniopropionate (DMSP) is an abundant and ubiquitous organosulfur molecule in marine environments with important roles in global sulfur and nutrient cycling. Diverse DMSP lyases in some algae, bacteria and fungi cleave DMSP to yield gaseous dimethyl sulfide (DMS), an infochemical with important roles in atmospheric chemistry. Here we identified a novel ATP-dependent DMSP lyase, DddX. DddX belongs to the acyl-CoA synthetase superfamily and is distinct from the eight other known DMSP lyases. DddX cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 65 publications
1
43
0
Order By: Relevance
“…The crystal structure and mechanism of DMSP cleavage of some DMSP lyase enzymes such as DddD, DddL, DddW and Alma1 are yet to be solved. (Landa et al, 2019;Li et al, 2021). Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The crystal structure and mechanism of DMSP cleavage of some DMSP lyase enzymes such as DddD, DddL, DddW and Alma1 are yet to be solved. (Landa et al, 2019;Li et al, 2021). Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Here, we have concentrated on most recent findings (Alcolombri et al, 2014;Hehemann et al, 2014;Li et al, 2014;Alcolombri et al, 2015;Brummett et al, 2015;Wang et al, 2015;Brummett and Dey, 2016;Sun et al, 2016;Li et al, 2017;Schnicker et al, 2017;Peng et al, 2019;Li et al, 2021).…”
Section: Dmsp Cleavage Pathwaysmentioning
confidence: 99%
“…(1,3 X2) and 1,3-xylotriose (1,3 X3) were collected for further use (Supplementary Figure 1). (Li et al, 2021). The pH was adjusted to 8.0 with HCl to keep consistence with that of the sampling sites (8.0-8.2).…”
Section: 3-xylan and 13-xylooligosaccharides Preparationmentioning
confidence: 99%
“…Liu et al (2018) demonstrated that many Alphaproteobacteria (mainly Roseobacters) and Actinobacteria can degrade DMSP. In addition, Li et al (2021) found DddX, a novel DMSP lyase, present in Firmicutes (i.e., Sporosarcina sp. P33) besides Gammaproteobacteria and Alphaproteobacteria.…”
Section: Dmsp Degradation By Dcbmentioning
confidence: 99%